Reliability (internal consistency) of the job content questionnaire on job stress among office workers of a multinational company in Kuala Lumpur - Maizura, H.; Masilamani, R.; Aris, T. (SAGE Publications, 2009)
This small, cross-sectional study assessed the reliability of 3 scales from the Job Content Questionnaire (JCQ)-decision latitude, psychological job demand, and social support-in a group of office workers in a multinational company in Kuala Lumpur. A universal sample of 30 white-collar workers from a department of the company self-administered the English version of the JCQ comprising 21 core items selected from the full recommended version of 49 items onsite. Reliability (internal consistency) was evaluated using Cronbach's alpha coefficients for each scale. Corrected item-total correlation was presented for each and every item. Cronbach's alpha coefficients were acceptable for decision latitude (. 76) and social support (. 79) but slightly lower for psychological job demand (. 64). Values for all item-total correlations for all 3 scales were greater than .3. In conclusion, this study suggests that the JCQ is a reliable scale for assessing job stress in this group of workers.